Cannabis and children: risk mitigation strategies for edibles - Conerney, Cathy; Steinmetz, Fabian; Wakefield, James; Loveridge, Sam (Frontiers in Psychiatry, 2024)
In the era of (re)legalisation of medicinal and recreational cannabis, accidental and intentional exposure to edibles, cannabis-infused food products, has increased substantially. However, there is particular concern regarding younger age groups. Most concerning is the increase in hospitalisations. According to a study by Myran et al. (1), provinces in Canada, where the sale of edibles is permitted, saw an increase in paediatric poisonings due to unintentional consumption of edibles. Similar trends have been observed in “legalised states” in the US, such as Colorado (2). The impact of using cannabis at an early age, but particularly the impact of accidental exposure to high THC quantities, may have negative mental or physical health outcomes. Whilst regulatory restrictions vary significantly from one legalised region to another, it is difficult to identify a best practice. The aim of this study is to identify and discuss new and existing risk mitigation strategies to give guidance to policymakers. Furthermore, practical aspects, such as compliance (e.g. audits by authorities), are discussed. It is noted that edibles have been around much longer than recent political attempts to regulate them.